2014
DOI: 10.4209/aaqr.2013.10.0312
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Soluble and Total Hexavalent Chromium in the Ambient Airborne Particles in New Jersey

Abstract: Hexavalent chromium (Cr(VI)) in ambient airborne particulate matter (PM) is a known pulmonary carcinogen and may have both soluble and insoluble forms. The sum of the two forms is defined as total Cr(VI). Currently, there were no methods suitable for large-scale monitoring of total Cr(VI) in ambient PM. This study developed a method to measure total Cr(VI) in ambient PM. This method includes PM collection using a Teflon filter, microwave extraction with 3% Na2CO3-2% NaOH at 95°C for 60 minutes, and Cr(VI) anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
(67 reference statements)
0
21
0
Order By: Relevance
“…The former include Na 2 CrO 4 , K 2 CrO 4 , and (NH 4 ) 2 CrO 4 ; the latter include PbCrO 4 , BaCrO 4 , and CaCrO 4 . Our recent work suggested that both groups were simultaneously present in the fresh ambient PM 10 collected in New Jersey and an aged reference urban PM (NIST 1648a) (Huang et al, 2014). The enriched 53 Cr(VI) spike used by EPA method 6800 (in the form of K 2 CrO 4 ) is only able to mimic the Cr(VI) with high solubility products (soluble Cr(VI)) in ambient PM.…”
Section: Discussion On the Application Of Epa Methods 6800 To Ambient mentioning
confidence: 99%
See 4 more Smart Citations
“…The former include Na 2 CrO 4 , K 2 CrO 4 , and (NH 4 ) 2 CrO 4 ; the latter include PbCrO 4 , BaCrO 4 , and CaCrO 4 . Our recent work suggested that both groups were simultaneously present in the fresh ambient PM 10 collected in New Jersey and an aged reference urban PM (NIST 1648a) (Huang et al, 2014). The enriched 53 Cr(VI) spike used by EPA method 6800 (in the form of K 2 CrO 4 ) is only able to mimic the Cr(VI) with high solubility products (soluble Cr(VI)) in ambient PM.…”
Section: Discussion On the Application Of Epa Methods 6800 To Ambient mentioning
confidence: 99%
“…The enriched 53 Cr(VI) spike used by EPA method 6800 (in the form of K 2 CrO 4 ) is only able to mimic the Cr(VI) with high solubility products (soluble Cr(VI)) in ambient PM. Therefore, we recommended separate measurement of soluble and total Cr (VI) in ambient PM (the difference between the two refers to insoluble Cr(VI)) (Huang et al, 2014), and EPA method 6800 can be used to correct soluble Cr(VI) conversion. In summary, the appropriate use of EPA method 6800 is important when measuring Cr(VI) in ambient PM.…”
Section: Discussion On the Application Of Epa Methods 6800 To Ambient mentioning
confidence: 99%
See 3 more Smart Citations